2017
DOI: 10.1007/s10792-017-0807-9
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vasculitis associated with cutaneous leukocytoclastic vasculitis

Abstract: We have reported the first case of clinically manifest retinal vasculitis, associated with a common form of cutaneous vasculitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Topical sCD83 treatment might inhibit the activation of DCs or trigger IDO expression in DCs, leading to suppressed T cell activation and infiltration, and thus reduces the damage of the eyes ( 28 , 40 ). However, we cannot exclude a more systemic effect since the eye is highly vascularized and drained by local lymph nodes ( 12 , 49 ). The mechanism of topical sCD83 treatment will be further elaborated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Topical sCD83 treatment might inhibit the activation of DCs or trigger IDO expression in DCs, leading to suppressed T cell activation and infiltration, and thus reduces the damage of the eyes ( 28 , 40 ). However, we cannot exclude a more systemic effect since the eye is highly vascularized and drained by local lymph nodes ( 12 , 49 ). The mechanism of topical sCD83 treatment will be further elaborated in the future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In this line, we show that sCD83 treatment leads to increased IDO and IL-10 expression in DCs, suggesting a shift to Treg induction. In addition, such tolerogenic DCs also might traffic through ocular compartments to the secondary lymphoid organs to promote systemic tolerance ( 5 , 49 ). Together, our data suggest that beneficial effects of sCD83 in EAU might be caused by a shift from stimulatory to tolerant DCs.…”
Section: Discussionmentioning
confidence: 99%
“… 12 In both studies, deposition of circulating immune complex had been suggested as a responsible mechanism of disease manifestation. 11 , 12 In this case, there were no systemic manifestations or abnormalities in blood evaluations to suggest an underlying systemic or infectious etiology. The response to IV methylprednisolone provided further support for an autoimmune process.…”
Section: Discussionmentioning
confidence: 67%
“… 22 Regarding the association of LCV and inflammatory ocular disease, Basu et al reported a case of retinal vasculitis, with the presentation of focal perivenular infiltrates and retinal hemorrhage, in a patient with LCV whose skin histology sample showed vessels with plump endothelial cells and neutrophilic infiltration and responded well to anti-inflammatory therapy. 11 In another study, Tsai et al described an LCV patient with the bilateral panuveitis and multifocal retinitis and vasculitis. 12 In both studies, deposition of circulating immune complex had been suggested as a responsible mechanism of disease manifestation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation